Tennis and the pandemic (Coaching and Sport Science Review, 2020)
The warrior within: Fortifying mental health in the COVID-19 pandemic (Janet A. Young & Alan J. Pearce (AUS)) Something new? Innovation post COVID-19. A must for tennis (Miguel Crespo & Jose Jabaloyes (ESP)) Let's go back to tennis! Playing tennis safe for everyone's health (Diego García (ARG)) Return to tennis guidelines (International Tennis Federation) Glimpsing new opportunities (César Kist (BRA)) Supervening impossibility of the provision of sports training and coaching due to the 'coronavirus' (Alejandro Valiño (ESP)) COVID-19 and its impact on players` mental health (E. Paul Roetert, Lydia Bell & Brian Hainline (USA)) Workplace learning and development in tennis coaching (Caio Cortela, Cesar Kist, Hugo Daibert, Alexandre Tozetto & Michel Milistetd (BRA)) Reopening of tennis clubs and solutions for changing consumer habits in the COVID-19 era (Cem Tinaz & Osman Emiroglu (TUR)) Coaching and coaches in the COVID-19 situation. The Polish perspective (Piotr Unierzyski & Tomasz Iwanski (POL)) Accommodate and adapt - Coaching in COVID-19 environment (Karl Davies, Butch Staples and Craig Morris (USA))